COMBINING ABILITY AND HETEROSIS ANALYSIS FOR SEED YIELD AND IT’S CONTRIBUTING TRAITS IN KARINGADA [Citrulus lanatus Citrulus lanatus Citrulus lanatus (Thumb) Mansf (Thumb) Mansf.] - SATYENDRA SINGH; S. D. SOLANKI; N. N. PRAJAPATI; BHARAT CHAUDHARY (The Bioscan, 2018)
A research was carried out using half diallel analysis of eight parents to identify the high heterotic crosses and their relationship in terms of general combining ability (GCA) and specific combining ability (SCA) in Karingada [Citrulus lanatus (Thumb) Mansf.] for seed yield . The analysis for combining ability revealed significant GCA and SCA mean sum of squares for all the characters which indicated the presence of both additive and non-additive gene actions.The GCA and SCA variance ratio revealed the preponderance of non-additive gene action for all the traits except for days to flowering and days to maturity. SKNK 903 was good general combiner for most of the characters including seed yield. The line MGPK-1 was also a good general combiner for cotyledon ratio and oil content. As per SCA effects, the crosses viz., SKNK 806 X SKNK 903 for seed yield per plant and SKNK 1004 X MGPK-1 for oil content were most promising. While among crosses, cross SKNK 806 X SKNK 903 was recorded highest magnitude of economic heterosis over the standard check GK 1 for seed yield and most of contributing traits.